Obstetrics, from The Original Text of Joseph B. De Lee. - Jacob Pearl Greenhill 1895- (USA W. B. Saunders Company, 1961)
Joseph Bolivar De Lee 1869-1942 Principles and Practice of Obstetrics . 1219 Illustrations on 903 Figures, 119 in Color
Keywords: Applied Sciences (3GdYdhe GdJWHjbjIs; General; Obstetrics